Case report: Novel junctional sarcoplasmic reticulum protein 1 intergenic region–anaplastic lymphoma kinase fusion in a patient with lung adenocarcinoma responds to alectinib - Xue, Feng; Xu, Shengyuan; Jiang, Cailing; Kang, Mafei; Usman, Muhammad; Zhu, Lin (Frontiers in Oncology, 2022)
Novel anaplastic lymphoma kinase (ALK) fusions are still being discovered in non-small cell lung cancer (NSCLC). Most patients with ALK+ NSCLC respond favorably to ALK tyrosine kinase inhibitors. In this case report, we identified a novel nonreciprocal ALK fusion, namely, junctional sarcoplasmic reticulum protein 1 (JSRP1) intergenic region–ALK fusion (Jintergenic: A20) via next-generation sequencing in a female patient initially diagnosed with stage IV B lung adenocarcinoma. Further examination of biopsy specimen and analysis of clinical samples by a multidisciplinary team confirmed the diagnosis of ALK+ NSCLC. At the 2- and 4-months follow-up after receiving alectinib, the patient responded rapidly, implying that alectinib had a remarkable therapeutic effect. We identified a novel JSRP1 intergenic region–ALK fusion as a carcinogenic mutation that responds to alectinib, thereby expanding the spectrum of ALK fusion partners in ALK + NSCLC. This study may help clinicians detect oncogenic mutations and provide timely treatment to patients with ALK+ NSCLC.